FTO in health and disease - Benak, Daniel; Sevcikova, Anezka; Holzerova, Kristyna; Hlavackova, Marketa (Frontiers in Cell and Developmental Biology, 2024)
Fat mass and obesity-associated (FTO) protein, a key enzyme integral to the dynamic regulation of epitranscriptomic modifications in RNAs, significantly influences crucial RNA lifecycle processes, including splicing, export, decay, and translation. The role of FTO in altering the epitranscriptome manifests across a spectrum of physiological and pathological conditions. This review aims to consolidate current understanding regarding the implications of FTO in health and disease, with a special emphasis on its involvement in obesity and non-communicable diseases associated with obesity, such as diabetes, cardiovascular disease, and cancer. It also summarizes the established molecules with FTO-inhibiting activity. Given the extensive impact of FTO on both physiology and pathophysiology, this overview provides illustrative insights into its roles, rather than an exhaustive account. A proper understanding of FTO function in human diseases could lead to new treatment approaches, potentially unlocking novel avenues for addressing both metabolic disorders and malignancies. The evolving insights into FTO’s regulatory mechanisms hold great promise for future advancements in disease treatment and prevention.